PENGARUH BAURAN PROMOSI TERHADAP OMZET PENJUALAN PRODUK KERAJINAN PURUN DI KABUPATEN HULU SUNGAI UTARA - Mailiana -; Diana Hayati (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2017)
Abstract,One key to successful application of the concept of marketing is understanding the needs, desires and behaviors of customers. To that end,The craftsmen of purun should be able to be willing to listen to voice of the customer (voice of the customer).The purpose of this study to analyze the effect of promotion mixs to sales volume. The method used multiple linear regression with SPSS Release tools and test validity and reliability. Dependent variable in this research is sales volume of purun’s product and independent variables are the five of promotion mixssuch as advertising, sales promotion, public relationship, personal selling and direct marketing.The results showed thatsimultaneous promotion mix has influence on the value of sales with multiple linear regression are Y = 2,919 + 0,062 X1+ 0,038 X2 +0,134 X3 + 0,097X4- 0,001 X5 . At t test where, the value of t of public relationship variables (X3) is the largest among the four variables other promotional mix, which is equal to 0,134.